Pengaruh Disiplin, Motivasi dan Penilaian Kinerja terhadap Kinerja Karyawan pada PMKS PT. Herfinta Farm & Plantation - Andri Supina Listy Hasibuan; Yahya Tanjung (BADAN PENERBIT STIEPARI PRESS, 2023)
This research aims to determine the influence of discipline, motivation and performance appraisal on employee performance at PMKS PT. Herfinta Farm & Plantation. The number of samples used in this research was 85 respondents. The data collection technique used in this research uses a questionnaire method, observation. The data sources used in this research use secondary and primary data sources. The testing techniques used in this research use research instrument tests, descriptive statistical tests, classical assumption tests, multiple linear regression tests and hypothesis tests. The results of this research show that the discipline variable has no effect on employee performance, while motivation and performance appraisal have a positive and significant effect on employee performance. Simultaneously the variables of discipline, motivation and performance appraisal influence employee performance.